META-ANALYSIS: THERAPEUTIC EFFECT OF TRANSCATHETER ARTERIAL CHEMOEMBOLIZATION COMBINED WITH COMPOUND KUSHEN INJECTION IN HEPATOCELLULAR CARCINOMA - Sun, Qizhe; Ma, Wenli; Gao, Yuan; Zheng, Whenling; Zhang, Bao; Peng, Yifei (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Compound Kushen Injection (CKI) is Sophora Flavescens and Heterosmilacis Japonicae extract. Meta-analysis confirmed that CKI plus transcatheter arterial chemoembolization (TACE) is more superior to TACE alone for unresectable hepatocellular carcinoma (UHCC) patients.